2020
DOI: 10.1038/s41388-020-01470-1
|View full text |Cite
|
Sign up to set email alerts
|

The Greatwall kinase safeguards the genome integrity by affecting the kinome activity in mitosis

Abstract: Progression through mitosis is balanced by the timely regulation of phosphorylation and dephosphorylation events ensuring the correct segregation of chromosomes before cytokinesis. This balance is regulated by the opposing actions of CDK1 and PP2A, as well as the Greatwall kinase/MASTL. MASTL is commonly overexpressed in cancer, which makes it a potential therapeutic anticancer target. Loss of Mastl induces multiple chromosomal errors that lead to the accumulation of micronuclei and multilobulated cells in mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…By this mechanism, phosphorylated substrates of mitotic kinases in the nucleus are presumably protected from premature dephosphorylation by PP2A-Tws between NEBD and mitotic exit. The identity of these substrates is still unclear, but they likely include the spindle assembly checkpoint kinase Mps1 and factors of the DNA damage-repair machinery ( Bisteau et al, 2020 ; Diril et al, 2016 ). Moreover, it would be interesting to explore if the spatiotemporal mechanism described here is essential for the ability of Gwl and Endosulfines to promote the G2/M transition in various systems (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…By this mechanism, phosphorylated substrates of mitotic kinases in the nucleus are presumably protected from premature dephosphorylation by PP2A-Tws between NEBD and mitotic exit. The identity of these substrates is still unclear, but they likely include the spindle assembly checkpoint kinase Mps1 and factors of the DNA damage-repair machinery ( Bisteau et al, 2020 ; Diril et al, 2016 ). Moreover, it would be interesting to explore if the spatiotemporal mechanism described here is essential for the ability of Gwl and Endosulfines to promote the G2/M transition in various systems (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…MASTL (microtubule-associated serine/threonine kinase-like) is the human orthologue of Drosophila Greatwall (Gwl) kinase 1,2 , a protein essential for mitosis 3 . Since its discovery, MASTL has become known as a master regulator of mitotic entry and integrity [4][5][6][7] . More recently, its roles have expanded to include meiosis 8-10 , recovery from DNA damage [11][12][13] , DNA replication 14 , platelet maturation 15,16 , cell migration and actomyosin contraction 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent efforts have been made to identify potential MASTL substrates with con icting results. Work by Bisteau et al 7 , identi ed 101 mitotic proteins that were dephosphorylated upon MASTL knockout in immortalized mouse embryonic fibroblasts (MEFs). Of these 6 were weakly phosphorylated in vitro by puri ed MASTL, but no decrease was observed using kinase dead MASTL, indicating that none are MASTL substrates 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule-associated serine/threonine kinase-like (MASTL), also known as Greatwall kinase, is a key mitotic kinase that regulates mitotic progression and maintains mitotic integrity [ 1 , 2 , 3 ]. MASTL controls the inactivation of the protein phosphatase 2A complex (PP2A-B55) by the directly phosphorylating its substrates, such as α-endosulfine (ENSA) and cAMP-regulated phosphoprotein 19, during mitosis and meiosis in mammalian somatic cells and oocytes, respectively [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that MASTL acts as an oncogenic kinase by inactivating tumor suppressive PP2A-B55 complex in breast cancer cells [11][12][13], thereby regulating various oncogenic properties, such as cellular transformation, chromosome instability, and Pharmaceuticals 2021, 14, 647. https://doi.org/10.3390/ph14070647 https://www.mdpi.com/journal/pharmaceuticals Pharmaceuticals 2021, 14, 647 2 of 12 metastasis [3,14,15]. MASTL targeting has reduced tumor growth in various in vitro and in vivo tumor models [13,16].…”
Section: Introductionmentioning
confidence: 99%